Tissue Culture-Based Strategies for Wheat (Triticum aestivum L.) Improvement: A Comprehensive Review - Patil, Pradip P.; Kadam, Shital (International Journal of Research in Interdisciplinary Studies, 2026)
Wheat (Triticum aestivum L.) is a major staple crop essential for global food security, yet its productivity is increasingly challenged by biotic and abiotic stresses, climate change, and limitations of conventional breeding. Tissue culture-based approaches have emerged as effective tools to accelerate wheat improvement and expand genetic variability. This review highlights the role of key tissue culture techniques, including callus culture, plant regeneration, somatic embryogenesis, in vitro selection for stress tolerance, and genetic transformation in wheat crop improvement. Callus culture and efficient regeneration systems underpin most biotechnological applications, enabling somaclonal variation, stress screening, and genetic manipulation. In vitro selection has been successfully used to develop wheat lines tolerant to salinity, drought, heat, and heavy metal stress under controlled conditions. In addition, advances in genetic transformation and genome editing technologies have facilitated precise improvement of traits related to stress tolerance, disease resistance, yield stability and grain quality. Despite existing challenges, the integration of tissue culture with modern biotechnological tools offers promising prospects for developing climate-resilient and high-yielding wheat cultivars.